Multi‐criteria decision‐making approach for modular enterprise resource planning sorting problems. Issue 5 (15th April 2021) - Carpitella, Silvia; Certa, Antonella; Izquierdo, Joaquín; La Cascia, Marco
Abstract: Implementing Enterprise Resource Planning (ERP) systems is currently recognized as a best practice with wide associated possibilities of business improvement for companies. Integrating these kinds of systems with business processes in the most efficient way requires to endeavour as much as possible simplifications for final users, which can be pursued by optimizing crucial software characteristics. The present article proposes a novel Multi‐Criteria Decision‐Making (MCDM) approach to deal with such an issue. Specifically, the ELECTRE (ELimination Et Choix Traduisant la REalité) TRI technique is suggested to assign ERP modules into predefined and ordered categories according to maintainability and usability, which are useful drivers in evaluating which module of an ERP software should be enhanced with priority. The results prove to have whole beneficial impact on system performance with relation to a case study: improvement evaluations will be identified based on the classes the ERP modules are assigned to by the method.